Asset allocation : - Gibson, Roger C. (McGraw-Hill, 2008)
In this Fourth Edition of his investing classic, Gibson once again offers techniques to design all-weather portfolios that improve long-term performance, while mitigating overall risks through widely varying market environments. rounded in the principles of modern portfolio theory, Gibson explains how and why asset allocation works. He demonstrates how adding new asset classes to a portfolio improves its risk-adjusted returns and how strategic asset allocation uses, rather than fights, the forces of capital markets to achieve investment success. Gibson also addresses the practical side of investing, advocating an approach based on a disciplined execution of the fundamentals-the most important things that investment professionals and lay investors need to focus on to achieve their financial goals. With more than two decades of experience managing clients' portfolios and expectations, he underscores the importance of identifying and working through the emotional and psychological traps that can impede investment success.